Analysis of Communication Skills and Empathy of Fifth-Grade Students of Elementary Schools through ICT-based Learning - Nurahman, Nurul Iman; Isnaeni, Wiwi; Ellianawati, Ellianawati (Journal of Primary Education)
The 21st-century skills are needed by students in learning and adapting to the rapid development of technology. This study aims to analyze the communication skills and students’ empathy after ICT-based learning. The method employed in this study was pre-experimental with one group pretest-posttest design. The sample consisted of 131 students in the fifth grade of primary schools. The techniques of data collection were observation and questionnaires. The data was analyzed using descriptive quantitative analysis. The results showed that the average score of communication skills for Sub Theme 1 to Sub Theme 3 lessons increased from 76 to The average score of students’ empathy for Sub Theme 1 to Sub Theme 3 lessons increased from 76 to 97. The results indicated that the average score of communication skills and students’ empathy was above the Minimum Mastery Criteria (>75). The students performed a positive response to ICT-based learning. Based on the results, it can be concluded that communication skills and empathy of the fifth-grade students of primary schools increase through ICT-based learning.